Positive images : gay men & HIV/AIDS in the culture of 'post crisis' - Kagan, Dion (Library of gender and popular culture, 2018)
A tidal wave of panic surrounded homosexuality and AIDS in the 1980s and early 90s. With the advent of antiretroviral drugs, however, the meaning of an HIV diagnosis changed radically. These transformative drugs enable people living with HIV to lead a healthy, regular life. But how has this shift impacted the representation of gay men and HIV in popular culture? Positive Images is the first detailed examination of how the relationship between gay men and HIV has transformed in the past two decades. From Queer as Folk to Chemsex, Dion Kagan examines literature and visual culture across the English-speaking world to unearth the socio-cultural foundations underpinning the 'post-crisis' period. His analyses provide acute insights into the fraught legacies of the AIDS crisis and its continued presence in the modern queer consciousness--back cover.